KAPASITAS PESANTREN DI KABUPATEN LUWU TIMUR - Israpil Israpil (Balai Penelitian dan Pengembangan Agama Makassar, 2017)
This paper intends to describe the capacity of pesantren in East Luwu Regency seenfrom three research problems, namely: how the distribution of pesantren along withits pattern and its variety and accessibility range; how the capacity of pesantrenrelated to the main pillars of pesantren such as kiyai / ustaz, students / students,books / teaching materials, mosques / mosques / places of worship, huts / dormitories,including other infrastructure; how the empowerment program and other supportingaspects. This study used descriptive qualitative method. The results showed that inEast Luwu Regency there are 16 boarding school institutions spread in 8 districtsfrom 11 districts, generally in rural areas. Related to the five main components ofpesantren in general have not been fulfilled. Especially the availability of santrimondok, lack of kiyai, pengajian pengajian of the book is no longer the main focus,ownership and procurement of the book is still very limited, but the existence of theboardingers still appear in terms of participating in educating students with thecharacteristics inherent in each boarding school. The empowerment of pesantrenfrom the economic side contributes greatly to the students and their caregivers aswell as the surrounding community, it is only seen from the sustainability of somepesantren is not running and the management has not been so focused and the lack ofgovernment involvement in its management